A systematic literature review on the rural-urban well-being gap in Europe - Cesare Meloni; Benedetto Rocchi; Simone Severini (Bio-based and Applied Economics, 2023)
A large amount of policy support is spent to foster the development of rural areas in Europe. However, empirical evidence on the well-being differential between rural and urban areas in Europe is scant and incomplete. The present study develops a systematic literature review on this topic, bridging a gap in research as a systematic analysis on the subject has not so far been developed as far as we know. It uses the Preferred Reporting Items for Systematic Reviews and Meta-Analyzes (PRISMA) method. The review focuses on type of definition of rural-urban most used in the literature, on main dimensions of well-being that are analyzed, on nature of the data and finally on main evidence that emerged regarding the differences in the various dimensions of well-being between rural and urban populations. The analysis confirms that available evidence is controversial and provides advice on how to develop new and better empirical analyses on this topic.